(3fXe GdeYdheGJ GdeMGSHjI (B/s - (3GHh NVQI, MSGe YHO Gddgs; (3YTjT, MSf SejQ s ((3YeGf(B: s (3ecJHI GdeLJeY GdYQHj(B, s, 2008)
(3ebOeI dOQGSI fXe GdeYdheGJ GdeMGSHjI , GdeYdheGJ h GJNGP GdbQGQGJ , JMdjd fXeGdeYdheGJ GdeMGSHjI h JUejegG h JfajPgG h JbjjegG, fXe EOGQI GdedaGJ GdeMGSHjI h fXe GOGQI bhGYO GdHjGfGJ , OhGaY h efGgL fWe GdeYdheGJ GdeMGSHjI , QbGHI CfXeI GdeYdheGJ GdeMhSHI (B.s
(3eQGLY U(B.169s
Keywords: (3GdeMGSHIs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s